Cryptic, alien and lost species: molecular diversity of Ulva sensu lato along the German coasts of the North and Baltic Seas. Issue 3 (3rd July 2019) - Steinhagen, S.; Karez, R.; Weinberger, F.
ABSTRACT: DNA barcoding analysis, using tuf A, revealed considerable differences between the expected and observed species inventory of Ulva sensu lato in the Baltic and North Sea areas of the German state of Schleswig-Holstein. Of 20 observed genetic entities, at least four ( U. australis, U. californica, U. gigantea and Umbraulva dangeardii ) had been introduced recently, whereas three others (one Ulva sp. and two Blidingia spp.) could not be identified at the species level and could also represent recently introduced species. In addition, the observed distributions of Kornmannia leptoderma and U. rigida were much more extensive than indicated by historical records, whereas Blidingia minima and Gayralia oxysperma were absent or much less common than expected. Barcoding analysis also revealed that both U. tenera (type material) and U. pseudocurvata (historical vouchers) from Helgoland, an off-shore island in the North Sea, actually belong to U. lactuca, a species that appears to be restricted to this island. Furthermore, past morphological descriptions of U. intestinalis and U. compressa have apparently been too restrictive and have been responsible for numerous misidentifications. The same is true for U. linza, which, in northern Germany, clusters into two genetically closely related but morphologically indistinguishable entities. One of these entities is present on Helgoland, while the second is present on North Sea and Baltic Sea mainland coasts.